The Effect of Profitability on the Value of Pharmaceutical Sector Companies Listed on the Indonesia Stock Exchange (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study aims to examine the effect of profitability on firm value in the pharmaceutical sector listed on the Indonesia Stock Exchange. This study uses secondary data from pharmaceutical companies listed on the IDX in 2014-2018. The research sample was taken using purposive sampling method, and analysis using linear regression analysis. From the results of the partial test (t test), the variable profitability has an effect on the value of the pharmaceutical sector companies listed on the Indonesia Stock Exchange.